High-tech crime fighters - "Walker , lou ann" (Parsippany : Globe Fearon, Pearson Learning Group, 2006)
"Crime Busters" delves into the world of Forensic Science and how it is used to catch criminals. -- "Clues from the Lab" describes how Forensic Science is used to help solve "Cold Cases" (unsolved or closed crimes)